Alopecia Areata: Burden of Disease, Approach to Treatment, and Current Unmet Needs - Alhanshali L; Buontempo MG; Lo Sicco KI; Shapiro J (Clinical, Cosmetic and Investigational Dermatology, 2023)
Lina Alhanshali,1 Michael G Buontempo,2 Kristen I Lo Sicco,3 Jerry Shapiro3 1Department of Dermatology, SUNY Downstate College of Medicine, Brooklyn, NY, USA; 2Department of Dermatology, Hackensack Meridian School of Medicine, Nutley, NJ, USA; 3The Ronald O. Perelman Department of Dermatology, NYU Grossman School of Medicine, New York, NY, USACorrespondence: Jerry Shapiro, The Ronald O. Perelman Department of Dermatology, New York University Grossman School of Medicine, 240 East 38th Street, 12th Floor, New York, NY, 10016, USA, Email jerry.shapiro@nyulangone.orgAbstract: Alopecia areata is an autoimmune hair loss disorder with variations in distribution, duration, and severity. The disease is chronic and often follows an unpredictable course, frequently leading to stress and anxiety for those who suffer from it. Throughout the years more knowledge has been gained regarding pathogenesis, diagnostic tools, impact on quality of life, as well as treatment strategies for alopecia areata. However, challenges in treating and alleviating the burden of disease remain. In this article, we discuss updates regarding the pathogenesis and treatment of alopecia areata and highlight unmet needs of the condition, including a review of limitations of current treatments, accessibility to management strategies, and the need for disease awareness and advocacy.Keywords: alopecia areata, disease burden, unmet needs